Clinicopathological features and outcomes of rare lung adenocarcinoma metastasis to the thyroid gland: A single‐center, 11‐year experience - Xuehan Gao; Zhen Cao; Xiayao Diao; Jiaqi Zhang; Ke Zhao; Libing Yang; Zhihong Qian; Xiaoyun Zhou; Chao Guo; Yeye Chen; Ziwen Liu; Shanqing Li (Thoracic Cancer)
Abstract Background Metastasis to the thyroid gland from lung adenocarcinoma is rare and challenging to diagnose due to similar histopathological features. This study aimed to analyze the clinicopathological characteristics of and treatment strategies for lung adenocarcinoma metastasis to the thyroid based on 11 years of institutional experience. Methods A retrospective study included patients with lung adenocarcinoma metastasis to the thyroid at our center from 2010 to 2023. Clinicopathological features and clinical outcomes were analyzed. Results Among 9714 lung adenocarcinoma patients, nine patients (five females, 55.6%) were diagnosed with thyroid metastasis, presenting primarily with cough symptoms. Most patients (88.9%) had synchronous tumors, whereas a minority (11.1%) had metachronous tumors. The median time from primary tumor diagnosis to metastasis was 4.8 months. Most patients developed bilateral thyroid metastases (88.9%). Diagnosis of thyroid metastasis was primarily through fine‐needle aspiration (FNA), with one case misdiagnosed as papillary thyroid carcinoma. Immunohistochemical staining revealed thyroid transcription factor‐1 (TTF‐1) and novel aspartic proteinase of pepsin family A (Napsin‐A) positivity and paired box 8 (PAX8) negativity. Genetic testing found epidermal growth factor receptor mutations in 71.4% of patients. The individualized comprehensive therapy included surgery, chemotherapy, immunotherapy, and targeted and supportive therapy. The median overall survival was 56.0 months, with a progression‐free survival of 12.7 months. Kaplan–Meier (K–M) analysis suggested improved survival with no advanced symptoms (p = 0.03) and targeted therapies (p = 0.05). Conclusions Lung adenocarcinoma metastasis to the thyroid is a rare disease, with an incidence of 0.1% among lung adenocarcinoma patients. Early treatment after symptom onset and personalized targeted therapies may improve prognosis. Despite rapid disease progression, favorable outcomes can be achieved with comprehensive treatment.